EFEKTIVITAS KONSELING MULTIBUDAYA DALAM MENINGKATKAN ADAPTASI SOSIAL DAN AKADEMIK SISWA DENGAN PENDEKATAN COUNSELING CULTURE DIVERSE - Rosianna, Elisabet; Nova Rizky; Albert Nainggolan; Yuda Zalfes Franata; Cinthya Angelica Vega (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Adolescence is a period experienced by every individual. The span of adolescence is 14-17 years. Cultural diversity in today’s society can potentially be an intervention strategy in addressing problematic adolescent behavior. This id influenced by counselors’ attachment to their own attributes. This approach is a framework that counselors use to understand and respond to cultural diversity in counseling.